STUDI PERHITUNGAN ALAT PENUKAR KALOR TIPE SHELL AND TUBE DENGAN MENGUNAKAN POLONOMIAL PANGKAT 4 (EMPAT) - Budiyono, Budiyono (Universitas Muhammadiyah Pekajangan Pekalongan, 2021)
To reduce production costs , designing a heat exchanger in advance is very effective than buying a ready - made exchanger . This design is in the form of dimensions of a shell and tube type heat exchanger using the polonomial power 4 calculation method and the calculation analysis method using the Exel program. Calculation of the dimensions of this heat exchanger aims to simplify the design and manufacture of heat exchangers. The heat exchanger designed is a shell and tube type heat exchanger which is widely used in Garment or Textile Companies in Pekalongan. The heat generated from the Diesel Exhaust Gas is 250 C - 300 C, where the exhaust gas originating from the Diesel is channeled to the heat exchanger so that the hot air released to the dryer has a temperature of 70C and the capacity of the dryer is 36 kg. /1 hour and Q = 1098 W and a temperature of 70 oC, so that the design of a heat exchanger is needed to circulate the hot air that has been raised in temperature. The exhaust gas that comes from PLTD with a mass flow rate of 2.72 kg/s, the design of a heat exchanger with shell and pipe type, where the flue gas heat flows through the shell and air through the pipe. Keywords: Heat Exchanger, Power Polonomial, DimensionKeywords: Heat Exchanger, Power Polonomial, Dimension